Typhoon Impact and Crisis Management - Tang, Dan Ling.; Sui, Guangjun; Lavy, Gad.; Pozdnyakov, Dmitry; Song, Y. Tony.; Switzer, Adam D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Major natural hazards have sparked growing public concern worldwide. This book provides new information on Typhoon Impacts and Crisis Management using satellite remote sensing technology, linking the natural sciences and social sciences in typhoon studies. It examines remote sensing observations of typhoons (Hurricanes), typhoon impacts on the environment, typhoon impacts on marine ecosystems, typhoon impacts and global changes, typhoon impacts on economics, and crisis management for typhoon disasters.
Part I Remote Sensing Observations of Typhoon (Hurricane) -- Part II Typhoon (Hurricane) Impacts on Environments -- Part III Typhoon (Hurricane) Impacts on Marine Ecosystem -- Part IV Typhoon (Hurricane) Impacts and Global Changes -- Part V Typhoon (Hurricane) Impacts on Economics -- Part VI Crisis Management for Typhoon (Hurricane) Disaster.
Keywords: Geography; Oceanography; Remote sensing; Geology; Marine Sciences; Earth Sciences; Natural Hazards; Meteorology; Remote Sensing/Photogrammetry.; Earth System Sciences; Oceanography; Marine & Freshwater Sciences